Exploring the relation between international experience and cross-borders innovation collaboration: case of Smes from Adriatic regions of Italy - Balboni, Bernardo; Bortoluzzi, Guido; Cozza, Claudio; Harirchi, Gouya; Pustrovrh, Aleš (Piccola Impresa / Small Business, 2016)
In the internationalization process, SMEs are constrained in two ways: liability of foreignness and liability of smallness. While the former is a barrier for all firms the latter is particularly related to SMEs. Extant literature acknowledges that the ability of SMEs to overcome the liability of foreignness is related to the acquisition of experiential market knowledge that allows SMEs to understand the causal linkages between actions and outcomes within the international environment. Furthermore, SMEs often have to compensate for internal resource deficiencies originating from their liability of smallness by seeking external resources both at the home location but also across the national boundaries. While both views on learning from and for exporting are complementary, their crossing impact measured through international growth is an effect still to be studied. Our paper aims at providing an understanding on the combinative effect of cross-border collaboration for innovation and international experience on international sales growth. In dealing with the research questions, this paper draws upon unique firm level survey data collected in 2014 across the Adriatic regions of Italy. Our results show how both international experience and international collaboration in innovation are positively associated to international sales’ growth. More in particular, for Italian SMEs, innovative collaboration with partners from Adriatic countries matters.